DEVELOPMENT OF STUDENT WORKSHEET WITH SAVI APPROACH TO IMPROVE MATHEMATICS REPRESENTATION ABILITIES IN CYLINDER MATERIALS - istiqomah, puji nur; Setiawan, Toto' Bara; Safrida, Lela Nur; Sugiarti, Titik; Murtikusuma, Randi Pratama (Kadikma, 2021)
This research aimed to develop a valid, practical, and effective worksheets with SAVI approach and can improve students' mathematical representation skills on cylinder material. The method of this research was a Research and Development (R and D) through the development of 4-D (Define, Design, Develop, and Disseminate). This research was conducted at SMP Negeri 1 Pace. The subjects of this research was 32 students of class IX. The results of the validation of the LKS with SAVI approach by the validator get an assessment of 3.8 after experiencing product revision. This shows that the LKS with SAVI approach that was developed is declared valid. The results of the analysis of the practicality of the LKS with SAVI approach were declared practical with the percentage of student response questionnaires of 85.03% and from the teacher's observation sheet of 87.5%. LKS with SAVI approach succeeded in increasing students' representation ability with a percentage increase of 90.625%. The result of the percentage of product completeness is 71.875% so it can be said that the LKS product with SAVI approach is an effective product. These results indicate that worksheets with SAVI approach are considered valid, practical, effective, and can improve mathematical representation skills.